2009
DOI: 10.1007/s10682-009-9304-6
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition deterring infochemicals in ladybirds: the role of phylogeny

Abstract: Faced with an ephemeral prey, aphidophagous ladybirds rely on the hydrocarbons present in the tracks of their larvae to choose an unoccupied patch for egg laying. Although both conspecific and heterospecific larval tracks might deter females from oviposition, the response to the later is often less striking. Several explanations have been suggested to account for this. In this paper we tested the phylogeny hypothesis, which predicts that the chemical composition of the tracks of closely related species of lady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
(53 reference statements)
1
29
0
Order By: Relevance
“…Magro et al. , ). In contrast, no attention was paid to patch assessment for oviposition of the relatively dull‐coloured, minute aphidophagous species of the Scymninae subfamily, although they are common in communities of aphid predators (Magro et al.…”
Section: Introductionmentioning
confidence: 99%
“…Magro et al. , ). In contrast, no attention was paid to patch assessment for oviposition of the relatively dull‐coloured, minute aphidophagous species of the Scymninae subfamily, although they are common in communities of aphid predators (Magro et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that increased habitat heterogeneity may enhance the potential for coexistence of H. axyridis with native aphidophagous predators by reducing intraguild interactions (Grez & Villagr an, 2000;Gardiner et al, 2009;Osawa, 2011). Furthermore, coccinellids often avoid laying eggs in areas with heterospecific cues (Magro et al, 2010) and spatial structure thereby provides benefits to adults that may use these alternative locations for oviposition. Furthermore, coccinellids often avoid laying eggs in areas with heterospecific cues (Magro et al, 2010) and spatial structure thereby provides benefits to adults that may use these alternative locations for oviposition.…”
Section: Introductionmentioning
confidence: 99%
“…The closing of the window is determined by the maturation of aphid colony (Kan, 1988a, b), as indicated by the presence of alate aphids (Kan & Sasakawa, 1986) and larval tracks (R ži ka, 2001a, 2003Magro et al, 2007Magro et al, , 2010. The inhibitory effect of the presence of conspecific larvae on oviposition was first reported in Adalia bipunctata (Linnaeus) (Hemptinne & Dixon, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The oviposition deterrence of larval tracks also extends to heterospecifics (R ži ka, 2001a;2003;Magro et al, 2007Magro et al, , 2010. The ODP primarily signals the presence and density of larvae in a patch, thereby allowing assessment of predation and cannibalism risk to eggs that may be laid (Martini et al, 2009;Moser et al, 2010;Meisner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation